Fiberglass spikes in the rehabilitative treatment of primary teeth treated with pulpectomy. Case report - Cárdenas - Flores, Carol Magaly (2020)
Fiber glass post serve as anchorage for the reconstruction of the lost dental stump. Providing elasticity comparable to dentin, when receiving occlusal loads in different directions, it flexes. This decreases the risk of internal stress in the duct, thus avoiding fractures and facilitating the total rehabilitation of teeth treated with pulpectomy.The objective of this case was to maintain the integrity of the deciduous teeth treated with pulpectomy by using the fiber glass post as a good option in pediatric dentistry for its simple management technique, its elasticity and the aesthetic results obtained